An Experimental Study of Thanatosis in Insects. - Saxena, S. C. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
In general an insect assumes a compact form by tightly pressing its legs and antennae to the body, while in a state of thanatosis. This posture is quite different from that assumed by dead insects. Generally at the termination of thanatosis the antennae are moved first and then the legs. Frequently repeated applications of the same stimulus lead to progressively shorter periods of thanatosis until insects no longer respond. Newly emerged beetles show a shorter duration of thanatosis in response to standard stimuli than the normal value attained when the individual ages. This result suggest some relations between tactile sensitivity and the development associated with the hardening and darjening of the cuticle. No differential sexual response was recorded. The duration of thanatosis increases with an increase in the duration of starvation. Newly emerged insects are more affected than senescent ones. It appears that besides the functioning of the head ganglia, the cooperation of other ganglia is necessary to bring about thanatosis. The thorax in Calandra granaria (L.) appears to be the part most sen-sitive to mechanical stimuli. The mid-legs are more sensitive than the fore and hind legs. On increasing the intensity of illumination the duration of thanatosis falls. On exposure to high intensity nervous excitability is induced: the duration of thanatosis also falls with increase in the period of irradiation by light. Calandra granaria (L.) appears to be most sensitive to blue and violet light: C. granaria and C. oryzae (L.) appear to perceive ultraviolet light. The duration of thanatosis diminishes with increase in temperature. At high temperatures insects show nervous excitability. An earlier termination of thanatosis takes place on subjecting coccinellids, while in a state of thanatosis, to radiant heat.